Edge-optimized machine learning models for real-time personalized health monitoring on wearables - Rafee, Athar Noor Mohammad; Dutta, Antu; Haque, Afsan; Rahman, Asif; Barua, Aditta (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.